Letter (copy) : International Solidarity Fund - Citrine, Walter, 1887-1983
029-0114-001 Sch/H. WMC/FC/EK/1229. Secretary's. 19th July, 1937. Mr W. Schevenels, International Federation of Trade Unions, 9, Avenue d'Orsay, Paris VIIe, FRANCE. Dear Mr. Schevenels, INTERNATIONAL SOLIDARITY FUND. Many thanks for your letter of the 16th instant and for forwarding a statement on the International Solidarity Fund. It is noted that you have been endeavouring to get the very latest figures for each country but you have not yet been able to get complete data. Yours sincerely, General Secretary. 292/946/29/114